Prompting Socially Shared Regulation of Learning and Creativity in Solving STEM Problems - Michalsky, Tova; Cohen, Avigail (Frontiers in psychology, 2021)
Problem-based learning (PBL) is a widely recommended method in science, technology, engineering, and mathematics (STEM) education through which students develop their scientific knowledge by collaboratively solving real-world problems. PBL benefits from both the activation of creative thinking and from socially shared regulation of learning (SSRL)-a group-level phenomenon whereby students collectively share common perceptions of their collaborative learning process and co-construction of knowledge. The current study examines the influence of three types of support (question prompts designed to promote SSRL, creative thinking, or a combination of both) on the participation of individuals in SSRL processes and on their knowledge acquisition, using a sample of 104 seventh-graders in accelerated science classes. Individuals' participation through the different stages of SSRL (forethought, performance, and reflection) was assessed using video recordings, and their scientific knowledge was measured through pre-and post-intervention knowledge tests. While all groups improved their scientific knowledge, individuals receiving only SSRL support improved their participation in most stages of SSRL compared with those receiving creativity or combined support, and a control group which received no support. The findings strengthen the case for SSRL-directed question prompts as a means to enhance student engagement in problem-solving tasks.